"Obvious" indications for Neural antibody testing in Epilepsy or Seizures: The ONES checklist. Issue 7 (18th April 2022) - Chang, Yiu‐Chia; Nouri, Maryam Nabavi; Mirsattari, Seyed; Burneo, Jorge G.; Budhram, Adrian
Abstract: Objective: Numerous predictive scores have been developed to help determine which patients with epilepsy or seizures of unknown etiology should undergo neural antibody testing. However, their diagnostic advantage compared to only performing testing in patients with "obvious" indications (e.g., broader features of autoimmune encephalitis, characteristic seizure semiologies) requires further study. We aimed to develop a checklist that identifies patients who have "obvious" indications for neural antibody testing and to compare its diagnostic performance to predictive scores. Methods: We developed the "Obvious" indications for Neural antibody testing in Epilepsy or Seizures (ONES) checklist through literature review. We then retrospectively reviewed patients who underwent neural antibody testing for epilepsy or seizures at our center between March 2019 and January 2021, to determine and compare the sensitivity and specificity of the ONES checklist to the recently proposed Antibody Prevalence in Epilepsy and Encephalopathy (APE2)/Antibodies Contributing to Focal Epilepsy Signs and Symptoms (ACES) reflex score. Results: One‐hundred seventy patients who underwent neural antibody testing for epilepsy or seizures were identified. Seventy‐four of 170 (43.5%) with a known etiology were excluded from sensitivity/specificity analyses; none had a true‐positive neural antibody. Of the 96 patients with an unknown etiology, 14 (15%) had a true‐positive neural antibody. The proportion of false‐positives was significantly higher among patients with a known etiology (3/3, 100%) compared to an unknown etiology (2/16, 13%; p  = .01). There was no significant difference of the APE2/ACES reflex score compared to the ONES checklist with regard to sensitivity (93% for both, p  > .99) or specificity (71% vs. 78%, p  = .18) for true‐positive neural antibodies. Significance: Compared to only performing neural antibody testing in patients with epilepsy or seizures of unknown etiology who have "obvious" indications, predictive scores confer no clear diagnostic advantage. Prespecified definitions of what constitutes a true‐positive neural antibody is required in future studies to avoid false‐positives that can confound results.